1993
DOI: 10.1038/hdy.1993.5
|View full text |Cite
|
Sign up to set email alerts
|

Experimental host-induced selection in Schistosoma mansoni strains from Guadeloupe and comparison with natural observations

Abstract: Allelic frequency variation at the malate dehydrogenase (E.C. 1.1.1.37) polymorphic locus (Md/i-i) was analysed during several successive generations in four strains of Schistosoma mansoni from Guadeloupe, maintained experimentally on mice. A rapid evolution of the frequency of the Mdh-1 a allele is interpreted as being the result of an interaction between experimental drift and selection induced by the murine laboratory host. These experimental results are compared to the genetic structures observed among the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…Such methodologies thereby facilitate the sampling of both miracidial and cercarial populations in the field, thus avoiding the introduction of sampling bias through the loss of alleles or genotypes by sampling error or host-induced selection in the subsequent population genetic analyses [14], [16][19].…”
Section: Introductionmentioning
confidence: 99%
“…Such methodologies thereby facilitate the sampling of both miracidial and cercarial populations in the field, thus avoiding the introduction of sampling bias through the loss of alleles or genotypes by sampling error or host-induced selection in the subsequent population genetic analyses [14], [16][19].…”
Section: Introductionmentioning
confidence: 99%
“…a higher proportion of eggs in the liver) in mice (Anderson & Cheever 1972) and a different pattern in monkeys (Powers & Cheever 1972). Rapid changes in isoenzyme patterns occur during successive generations of newly isolated S. mansoni strains in mice so that it is clear that genetic selection may occur rapidly in the laboratory (LoVerde et al 1985, Bremond et al 1993. Pinto et al (1997) recently documented the greater genetic variability in worms from field isolates compared to the LE strain long maintained in the laboratory.…”
Section: General Considerations In the Interpretation Of Models Of Scmentioning
confidence: 99%
“…Some mammals, such as foxes and rabbits, are absolutely resistant (Von Lichtenberg et al, 1962; Peck et al, 1983), while others demonstrate selection of certain S. mansoni genotypes (LoVerde et al, 1985; Bremond et al, 1993). Although rats of the species Rattus rattus can maintain the life cycle, R. norvegicus cannot (Alarcón de Noya et al, 1997).…”
mentioning
confidence: 99%
“…Previous studies have reported selection for particular S. mansoni alloenzyme alleles when S. mansoni populations from baboons (LoVerde et al, 1985) and rats (Bremond et al, 1993) were maintained in laboratory mice. Since at least one of the allozymes selected against may be antigenic in mice and provoke an immune response (Bremond et al, 1993), these studies are not directly relevant to our work with neutral markers.…”
mentioning
confidence: 99%
See 1 more Smart Citation